Effect of ABCG2, OCT1, and ABCB1 (MDR1) gene expression on treatment-free remission in a EURO-SKI subtrial - Rinaldetti, Sébastien; Spiess, Birgit; Seifarth, Wolfgang; Fabarius, Alice; Hofmann, Wolf-Karsten; Saußele, Susanne (Clinical lymphoma & myeloma, 2018)
Introduction - Tyrosine kinase inhibitors (TKIs) can safely be discontinued in chronic myeloid leukemia (CML) patients with sustained deep molecular response. ABCG2 (breast cancer resistance protein), OCT1 (organic cation transporter 1), and ABCB1 (multidrug resistance protein 1) gene products are known to play a crucial role in acquired pharmacogenetic TKI resistance. Their influence on treatment-free remission (TFR) has not yet been investigated. - Materials and Methods - RNA was isolated on the last day of TKI intake from peripheral blood leukocytes of 132 chronic phase CML patients who discontinued TKI treatment within the European Stop Tyrosine Kinase Inhibitor Study trial. Plasmid standards were designed including subgenic inserts of OCT1, ABCG2, and ABCB1 together with GUSB as reference gene. For expression analyses, quantitative real-time polymerase chain reaction was used. Multiple Cox regression analysis was performed. In addition, gene expression cutoffs for patient risk stratification were investigated. - Results - The TFR rate of 132 patients, 12 months after TKI discontinuation, was 54% (95% confidence interval [CI], 46%-62%). ABCG2 expression (‰) was retained as the only significant variable (P = .02; hazard ratio, 1.04; 95% CI, 1.01-1.07) in multiple Cox regression analysis. Only for the ABCG2 efflux transporter, a significant cutoff was found (P = .04). Patients with an ABCG2/GUSB transcript level >4.5‰ (n = 93) showed a 12-month TFR rate of 47% (95% CI, 37%-57%), whereas patients with low ABCG2 expression (≤4.5‰; n = 39) had a 12-month TFR rate of 72% (95% CI, 55%-82%). - Conclusion - In this study, we investigated the effect of pharmacogenetics in the context of a CML treatment discontinuation trial. The transcript levels of the efflux transporter ABCG2 predicted TFR after TKI discontinuation.